(2√3-3√2)²,qual a resoluçao???
Soluções para a tarefa
Respondido por
1
Olá, boa noite!
![(2\sqrt{3}-3\sqrt{3})^2=\\(-1\sqrt{3})^2=\\(-1)^2\cdot(\sqrt{3})^2=\\1\cdot3=\\3 (2\sqrt{3}-3\sqrt{3})^2=\\(-1\sqrt{3})^2=\\(-1)^2\cdot(\sqrt{3})^2=\\1\cdot3=\\3](https://tex.z-dn.net/?f=%282%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D%29%5E2%3D%5C%5C%28-1%5Csqrt%7B3%7D%29%5E2%3D%5C%5C%28-1%29%5E2%5Ccdot%28%5Csqrt%7B3%7D%29%5E2%3D%5C%5C1%5Ccdot3%3D%5C%5C3)
Espero ter ajudado.
Bons estudos! :)
Espero ter ajudado.
Bons estudos! :)
ilanaoliveira719:
o resultado tem que ser 30-12 raiz de12
Perguntas interessantes